CARBON STORAGE IN SEAGRASS BEDS IN THE LITORAL ZONE OF SANCANG BEACH, GARUT - Dedi Koswara; Diana Hernawati; Diki Muhamad Chaidir (Universitas Medan Area, 2023)
The vast expanse of seagrass beds in coastal areas can provide many ecosystem services, one of which is the ability of seagrass beds to absorb and store carbon dioxide (CO2). Carbon dioxide gas (CO2) is one of the components of greenhouse gases that contribute to global warming. So the role of seagrass is very important in the ecosystem. This study aims to determine carbon storage in seagrass in the littoral zone of Sancang Beach, Garut Regency, which was carried out in April-June 2022. Determination of potential carbon storage was carried out by taking seagrass samples with a size of 20 cm x 20 cm, then drying to a constant weight. and calculated using a carbon conversion factor for seagrass biomass of 0.34. The results showed that the carbon content at Station 1 Cibako (145.9331 g C/m2) was higher than Station 2 Cikujangjambe (110.026 g C/m2) and Station 3 Ciporeang (117.771 g C/m2). The average carbon content at Sancang beach is 124,577 g C/m2. The conclusion is that in general the carbon storage below the substrate (below ground) in seagrass in the Litoral Zone of Sancang Beach has a greater value than the value of carbon storage above the substrate (above ground).